1992
DOI: 10.1575/1912/2987
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll diagenesis in the water column and sediments of the Black Sea

Abstract: This thesis examines the degradation pathways of chlorophyll in the Black Sea water column and sediments. Measurements are made of total chlorophyll in sediment traps from two locations and depths in the water column, and at two locations in surface sediments. Individual chlorophyll degradation products are also identified. This data is used to construct a mass balance of chlorophyll production and sedimentation showing the major pathways for chlorophyll loss and the ultimate sedimentary sinks. The distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…cholesteryl While this problem may not be significant in recent sediments, it could become more significant in sediments heavily affected by diagenesis. [4] Recent studies of zooplankton grazing and senescence-induced changes [Harradine et al, 1996;King and Wakeham, 1996;7libot et al, 1999a, 1999b have confirmed the finding of King andRepeta [ 1991, 1994] that CSEs are formed during zooplankton herbivory when the sterols produced by phytoplankton become esterified to pyropheophorbide-a, a chlorin. Several studies suggest that the conversion of sterols to CSEs occurs nonselectively during the grazing process [King and Repeta, 1991;Harradine et al, 1996;Talbot et al, 1999a].…”
Section: Future Directionsmentioning
confidence: 88%
See 4 more Smart Citations
“…cholesteryl While this problem may not be significant in recent sediments, it could become more significant in sediments heavily affected by diagenesis. [4] Recent studies of zooplankton grazing and senescence-induced changes [Harradine et al, 1996;King and Wakeham, 1996;7libot et al, 1999a, 1999b have confirmed the finding of King andRepeta [ 1991, 1994] that CSEs are formed during zooplankton herbivory when the sterols produced by phytoplankton become esterified to pyropheophorbide-a, a chlorin. Several studies suggest that the conversion of sterols to CSEs occurs nonselectively during the grazing process [King and Repeta, 1991;Harradine et al, 1996;Talbot et al, 1999a].…”
Section: Future Directionsmentioning
confidence: 88%
“…[5] After their formation in the water column, CSEs and other chlorins arrive at the seafloor via fecal pellets [King, 1993;Talbot et al, 1999a]. Within sediments, CSEs exhibit enhanced preservation relative to both other chlorins [Talbot et al, 1999a, and references therein] and free sterols [King and Repeta, 1991, 1.994;Talbot et al, 2000].…”
Section: Formation Of Cses In the Marine Environmentmentioning
confidence: 99%
See 3 more Smart Citations